Resiliência e antifragilidade em cadeias de suprimentos: impactos da pandemia de covid 19 no abastecimento de um hospital público do Triângulo Mineiro - Gomes, Túlio Gonçalves (2023)
Purchasing and supply chain management was affected in several aspects by Covid-19, and recent studies have addressed the impacts of the pandemic on the supply chains of various segments. Resilience is essential for these chains to recover as quickly as possible and return to their original state, but in complex contexts such as pandemics, it may not be enough. Thus, from Taleb's (2012) antifragile concept, a new concept of antifragile supply chain emerges, defined by Nikookar, Varsei and Wieland (2021) as a living supply chain that can gain from disorder, and that must be dynamic and fluid, not static, evolving with the unpredictable disorder inherent in today's business world. In this sense, the general objective of this thesis was to identify how resilience factors contribute to the construction of an antifragile supply chain, considering Taleb's theory of antifragility (2012), from the impacts caused by the Covid-19 pandemic. To this end, a case study was carried out with a University Hospital of Triângulo Mineiro as the focal organization, and two suppliers. 20 professionals were interviewed, 12 managers of the focal organization, 2 representatives of suppliers, and 6 employees of the Hospital's assistance area. From these interviews, a content analysis was carried out that obtained 4 categories: 1) Ruptures; 2) Resilience Factors; 3) Antifragility Maturity Levels; and 4) Action by the Public Power. A Likert-scale quiz was also applied to 57 employees of the focal organization, in addition to the interviewed managers. The results show that, despite the supply chain of hospital supplies having evolved in many internal processes of organizations during the pandemic, it is not possible to state that the chain studied is antifragile. The results also indicate which resilience factors best contributed to the chain's resilience throughout the pandemic, and which factors need to be strengthened in the search for an anti-fragile supply chain. In this sense, in meeting the proposed objectives, six propositions were suggested: people's actions, and the poor management of available financial resources, can enhance the effects of disruptions caused by unexpected events such as the pandemic; collaboration plays a central role in generating other resilience factors such as flexibility, adaptability, agility and visibility, generating organizational resilience and providing supply chain resilience; in black swan events such as the pandemic, the role of governance as an inducer of good practices, local supply strategies and centralized sharing of purchases and supplies contribute to the resilience of the chain; improving internal communication channels and throughout the supply chain is essential in the search for antifragility; the hospital supplies supply chain must invest in the search for redundancy, visibility and agility, aiming to reach the maturity level of an antifragile chain; and to reach the maturity of an antifragile chain, in addition to resilience factors, it is necessary to invest in regulations that make the purchasing processes of public organizations more flexible.